Incorporation Image in M-OPAC to Support Book Identification - Farha Dalilah, Hashim (2009)
The growth and rapid evolution of the wireless technology have created new opportunities for anytime and anywhere library services. As a result, numerous mobile library services have been developed to gain the advantages of it. Nonetheless, there is no research and exploration has been initiated in proposing mobile library application that incorporates images of books to support the identification of the required books.Thus, this work seeks to present M-OPAC, a mobile library application which incorporates images in the book description. The evaluation phase undertaken in this work identifies whether the presentation of images paired with text description could assist users in identifying the exact book. In order to rate the usefulness of M-OPAC, a total of 30 participants were given the opportunity to test the prototype application.Analysis of data gathered from questionnaire given after the test of the prototype application was also discussed in this report. The findings indicate that most of the participants preferred images paired with text result, compared to presenting the search result as a plain ranked list.